2023
DOI: 10.1021/acs.orglett.3c00741
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura Cross-Coupling of 2-Pyridyl Trimethylammonium Salts by N–C Activation Catalyzed by Air- and Moisture-Stable Pd–NHC Precatalysts: Application to the Discovery of Agrochemicals

Abstract: We report the first Suzuki−Miyaura cross-coupling of 2-pyridyl ammonium salts by highly selective N−C activation catalyzed by air-and moisture-stable Pd(II)−NHC (NHC = Nheterocyclic carbene) precatalysts. The use of well-defined and highly reactive [Pd(IPr)(3-CF 3 -An)Cl 2 ] (An = aniline) or [Pd(IPr)(cin)Cl] (cin = cinnamyl) Pd(II)−NHC catalysts permits an exceptionally broad scope of the cross-coupling to furnish valuable biaryl and heterobiarylpyridines that are ubiquitous in medicinal chemistry and agroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…When the molar ratio of 1a and 2m was controlled as 1 : 1, the monosubstituted compound 3p was obtained by the Sonogashira reaction. Importantly, the molecular structure and purity of all obtained 3a–3p were well demonstrated by 1 H, 19 F, 13 C NMR, 27,28 HRMS (Fig. S1–S62, ESI†) and single-crystal X-ray diffraction analysis (for compounds 3e , 3f , 3m and 3p , Tables S1–S4, Fig.…”
Section: Resultsmentioning
confidence: 72%
“…When the molar ratio of 1a and 2m was controlled as 1 : 1, the monosubstituted compound 3p was obtained by the Sonogashira reaction. Importantly, the molecular structure and purity of all obtained 3a–3p were well demonstrated by 1 H, 19 F, 13 C NMR, 27,28 HRMS (Fig. S1–S62, ESI†) and single-crystal X-ray diffraction analysis (for compounds 3e , 3f , 3m and 3p , Tables S1–S4, Fig.…”
Section: Resultsmentioning
confidence: 72%
“…However, in contrast to the synthesis of 2-arylpyridines, which are readily synthesized by the biaryl Suzuki cross-coupling of appropriate precursors, the synthesis of 2-alkylpyridines remains a significant challenge due β-hydride elimination degrading the organometallic reagent and slower transmetalation step. , Critically, the presence of the basic pyridine nitrogen often coordinates to the metal and slows down the already challenging alkylative catalytic cycle . Further, the competing β-hydride elimination of alkyl organometallics leads to the formation of olefins, which undergo reinsertion, resulting in regioselectivity issues .…”
mentioning
confidence: 99%
“…Preliminary selectivity studies to gain insight into the reaction mechanism were conducted (Scheme ). (1) Intermolecular competition experiments using differently substituted organoboranes showed that electron-rich nucleophiles are more reactive ( n -C 10 H 21 : n -(CH 2 ) 3 C 6 F 5 > 95:5), which is consistent with faster transmetalation. , (2) Interestingly, competition experiments using alkyl vs Ar nucleophiles showed that alkyl organoboron reagents are more reactive under these conditions ( n -C 10 H 21 :Ph = 64:36), which bodes well for the future development of Pd(II)–NHC-catalyzed alkylative Suzuki cross-couplings of unconventional electrophiles. Mechanistically, it should be noted that the pyridine nitrogen is likely involved in assisting oxidative addition.…”
mentioning
confidence: 99%
See 2 more Smart Citations